Imaging Spectrometers, Sensors, Systems, and Missions - Pu, Ruiliang (Hyperspectral Remote Sensing, 2017)
This chapter introduces the working principles, technical characteristics, and status of current/operational and future airborne and spaceborne hyperspectral sensors, systems, and missions. Imaging spectrometers can typically use a 2D matrix array to produce a 3D data cube. The pushbroom imaging sensor uses a 2D charge couple device (CCD)-area array of detectors, one dimension for spectral and the other for spatial at the focal plane of the spectrometer. The number of pixels equals that of ground cells for a given swath. Airborne Imaging Spectrometer for Different Applications (AISA) is a commercially available hyperspectral imaging spectrometer from Spectral Imaging Ltd. of Finland. The objective of developing the AISA is to provide users with a wide variety of application configurations. It operated at the beginning of 1993. AISA is a programmable pushbroom imaging spectrometer based on CCD technology. The first sensor array used was an intensified CCD type TV camera.